2020
DOI: 10.1097/rlu.0000000000003182
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Duo–Peptide Receptor Radionuclide Therapy With Indigenous 90Y-DOTATATE and 177Lu-DOTATATE in Large-Volume Neuroendocrine Tumors

Abstract: The efficacy of 177Lu-DOTATATE in large neuroendocrine tumors (NETs) is reduced because of the lower energy (Eβmax 0.497 MeV) and shorter range of 177Lu. The pure β-emitter 90Y with its longer β range is more effective in larger tumors. This should be balanced with the greater risk of 90Y-DOTATATE–related nephrotoxicity. Sequential duo–peptide receptor radionuclide therapy may result in a better response with minimal adverse effects in large-volume heterogeneous NETs. A 56-year-old man with large rectal NET li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…6,9 Peptide receptor radionuclide therapy (PRRT) using 177 Lu-DOTATATE, 177 Lu-DOTATOC, and 90 Y-DOTATATE, has also been well documented for the treatment of gastroenteropancreatic (GEP) NETs. [10][11][12] The NETTER-1 trial confirmed that PRRT improved the outcomes of patients with midgut NETs, and was better tolerated with fewer adverse effects compared to long-acting octreotide therapy. 13,14 However, growing evidence has indicated that NET does not always respond well to PRRT alone, and identifying combined therapies with optimal clinical efficacy remains a major challenge for clinicians.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…6,9 Peptide receptor radionuclide therapy (PRRT) using 177 Lu-DOTATATE, 177 Lu-DOTATOC, and 90 Y-DOTATATE, has also been well documented for the treatment of gastroenteropancreatic (GEP) NETs. [10][11][12] The NETTER-1 trial confirmed that PRRT improved the outcomes of patients with midgut NETs, and was better tolerated with fewer adverse effects compared to long-acting octreotide therapy. 13,14 However, growing evidence has indicated that NET does not always respond well to PRRT alone, and identifying combined therapies with optimal clinical efficacy remains a major challenge for clinicians.…”
Section: Introductionmentioning
confidence: 96%
“…Somatostatin receptors are a hallmark of NETs, and 68 Ga‐labeled somatostatin analog positron emission tomography/computed tomography (PET/CT) imaging is the gold standard for the detection of well‐differentiated NETs 6,9 . Peptide receptor radionuclide therapy (PRRT) using 177 Lu‐DOTATATE, 177 Lu‐DOTATOC, and 90 Y‐DOTATATE, has also been well documented for the treatment of gastroenteropancreatic (GEP) NETs 10–12 13,14 .…”
Section: Introductionmentioning
confidence: 99%